MARKETING PERFORMANCE ANALYSIS OF BUILDING PLANNER CONSULTANT - Surachman Surjaatmadja (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya(STIESIA) Surabaya, 2010)
Marketing Performance Analysis of Building Planner Consultants. (case study in Java). Competition in the industry is becoming very keen,. to win this competition company needs implementative and adaptive marketing program and strategy to deliver the product or service, so that the customer accepts it better than the competitors (superior). The service marketing mix program which have been selected from the market informations, coordinated and colaboration with all of function in the company will give result better. This research aims: To analyze of marketing performance of building planner consultants in Java. The service marketing mix program as marketing planning, segmenting, targeting, positioning, product/services, pricing, promotion, channel distribution, physical evidence, people and price. This research is used the strategic marketing management approach. The characters of this research is descriptive, while research method is survey explanatory, by using the sampling technique of simple random sampling to 140 of Building Planner Consultants. Results of this research indicate that about the marketing planning activities more of firm (about 90%) never do it, only 15.0% they doing the segmentation and 71.42% sometimes they do